The Influence of Social Media, Family Religious Education, School Religious Environment, and Religiosity on High School Students' Morality in Pekanbaru - Rahayu, Evi; Neni, Neni; Siregar, Maralottung (Jurnal Pendidikan Progresif, 2025)
The Influence of Social Media, Family Religious Education, School Religious Environment, and Religiosity on High School Students' Morality in Pekanbaru. Objective: This study investigates the influence of social media, family religious education, school religious environment, and personal religiosity on the morality of students in private Islamic senior high schools in Pekanbaru. The focus is on understanding how both internal and external factors interact to shape students’ moral values, particularly in the context of increasing digital media exposure. Methods: A quantitative research approach with a correlational design was employed. The population included students from several private Madrasah Aliyah (Islamic senior high schools) in Pekanbaru. Data collection was conducted using validated questionnaires to ensure accuracy and reliability. Statistical analyses included descriptive statistics to summarize the data, Pearson correlation to measure the strength and direction of relationships among variables, and multiple linear regression to determine the combined predictive power of the independent variables. All analyses were performed using SPSS software. Findings: The results revealed that all four independent variables had significant positive correlations with students’ morality. Among them, personal religiosity emerged as the strongest predictor, suggesting that an individual’s internalized religious beliefs and practices play a central role in moral behavior. This was followed by family religious education, highlighting the importance of parental guidance in shaping moral character. Social media showed a positive but less dominant influence, indicating its potential role in reinforcing moral values when used constructively. The school religious environment also contributed positively, though to a lesser extent than the other factors. The regression model was statistically significant, with an R² value of 0.575, meaning that 57.5% of the variation in morality could be explained by these four predictors. Conclusion: The study concludes that students’ moral development is influenced by a combination of internal factors (such as personal religiosity) and external factors (including family, school, and social media). These findings underscore the importance of collaborative efforts among families, schools, and society to promote moral values, especially in today’s digital age. Keywords: morality, social media, family religious education, school religious environment, personal religiosity.